ANALYSIS AND OPTIMIZATION ON VEHICLE LOW SPEED BACK-CRASH DESIGN BASED ON RCAR TESTS - ZHANG Yu; ZHENG ShengWei (Jixie qiangdu)
Taking a hatchback car as example in this paper,introduced the RCAR low speed crashworthiness test and evaluation methods. Then taking panel-rear out and C-shaped pillar as research objects,discussed the methods of vehicle low speed crash optimization design,through the experimental verification,effectively improved than optimization before.